Onion and Apple Functional Ingredients Intake Improves Antioxidant and Inflammatory Status and Vascular Injury in Obese Zucker Rats - Claudia Balderas; Javier Angulo; Alejandro Sevilleja-Ortiz; Concepción Peiró; Susana Vallejo; Pilar Dongil; Begoña de Ancos; Concepción Sánchez-Moreno (MDPI AG, 2022)
The objective of this study was to investigate the effects of onion and apple functional ingredients in homozygous (fa/fa) obese Zucker rats. Rodents were fed three diets: standard diet [obese control (OC) group], standard diet containing 10% onion [obese onion 10% (OO) group] and standard diet containing 10% apple [obese apple 10% (OA) group] for 8 weeks. Food intake and body weight gain were higher in obese than in lean rats. Food efficiency was lower in OO and AO groups compared with OC group. Within the obese groups, total cholesterol, LDL-cholesterol, triacylglycerols, glucose, insulin and triglyceride-glucose index were lower in OO group than in OC group, and HDL-cholesterol was higher in OO group than in OC group. In general, antioxidant activity (ABTS•+ and FRAP), antioxidant enzyme activities (CAT, SOD, GPx), GSH/GSSG ratio, nitrate/nitrite and GLP-1 increased in OO and OA groups compared with OC. Oxidative stress biomarkers, namely protein carbonyls, 8-hydroxy-2'-deoxyguanosine, 8-epi-prostaglandin F2α, inflammatory and vascular injury biomarkers (PAI-1, TIMP-1, VEGF, sICAM-1, sE-Selectin, MCP-1) and leptin, were lower in OO and OA groups than in OC group. Endothelial impairment was partially reversed, and superoxide content and gene expression of NLRP3, NFKβ1 and COX2 decreased, in OO and OA groups with respect to OC group. The study demonstrates that high pressure-processed onion and apple functional ingredients administration to obese Zucker rats causes beneficial effects on metabolic health, in particular through improving food efficiency ratio; exerting pronounced lipid-lowering effects; reducing glycemia, insulinemia, and biomarkers of hepatic injury (ALT, AST); improving antioxidant, oxidative stress, inflammatory and vascular injury biomarkers, metabolic hormones, and endothelial function; and decreasing proinflammatory gene expression of NLRP3, NFKβ1 and COX2.